Girl reserves at tables in downstairs lounge - Unknown:::Creator::::::::::::
This photograph shows a large group of women and youth seated around dining tables and standing along the wall in the downstairs lounge. Present are Doris Elden, Eveloy Miller Berger, Miss Corneili Farley, Peare Eberhard Belloli, Connie Stalker Ponnichesen, Jewel Smith McKenna(?), Jean Libby, Marion Oldham, Beth Place. Many of those present are dressed in Girl Reserves uniforms.